Analisis Reduplikasi dalam berita di koran harian KOMPAS edisi 25 April 2024 - Arni Yuniar Prastika; Muhitotun Nadhifah; Mulia Putri Khasanah; Rafika Dini; Wawan Hermawan (STIKes Ibnu Sina Ajibarang, 2024)
In this research, the researcher aims to find out more about reduplication which is usually used in writing news in newspapers, so that readers will be interested in reading and it will be easier for them to understand the information in the news. This research also aims to analyze a reduplication of news in the April 25 2024 edition of the Kompas daily newspaper. The method used is a qualitative descriptive method. The data source in this research is a news story in the April 25 2024 edition of the Kompas Daily Newspaper. The data obtained in this research is in the form of a word/quote. The technique used to collect data is in the form of observation techniques. And here are the steps for analyzing the data in this research: (1) analyzing the information obtained from the news in the newspaper, (2) recording the data and then making a summary of the data, (3) presenting the results of the analysis in the form of a description. The results of this research are to find out the redundancy contained in a news item in the April 25 2024 edition of the Kompas Daily Newspaper.